ALT DUDAK TAM KAYIPLARININ iKi YANLI 'FAN FLEP' iLE ONARIMI - AYGIT, Ahmet Cemal; GÜZEL, M.Zeki; BAYRAMİÇLİ, M.; AYDIN, Yağmur; YÜCEL, Akın (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Reconstruction of large defects of the lower lip continue to be formidable challenge. Total excision of the lower lip is rarely necessary, so many surgeons' experience in repair of this size defect is limited. In this paper, we described the reconstruction of total lower lip defects using bilateral fan flaps without mucosal flap or graft. Results.- We had wsed bilateral fan flap reconstructions for total lower lip defects in 17 patients. Only two patients were not able to use dentures after the operation. In other 15 patients, the aesthetic and functional goals were achiewd. Conclusion.- The technique of total lower lip reconstruction with bilateral fan flap was further refined in this report.